Probability-based heuristic content placement method for ICN caching - Hai-bo WU; Jun LI; Jiang ZHI (Tongxin xuebao)
A probability-based heuristic caching strategy(PCP)was proposed.The major idea was that relevant informa-tion was collected when the interest and data packet are transmitted.When the data packet is returned back,on-path cache nodes decide whether to cache the content with certain probability.The probability is associated with the content popu-larity and placement benefit,i.e.,proportional to content popularity and content placement benefit.The experimental re-sults indicate PCP can achieve salient performance gain in terms of cache service ratio,cache hit ratio,access latency ra-tio,compared with current strategies.Meanwhile,PCP's overhead is affordable.